A Mechanistically Inspired Halenium Ion Initiated Spiroketalization: Entry to Mono‐ and Dibromospiroketals. (10th January 2022) - Ashtekar, Kumar Dilip; Gholami, Hadi; Moemeni, Mehdi; Chakraborty, Ankush; Kiiskila, Lindsey; Ding, Xinliang; Toma, Edmond; Rahn, Christopher; Borhan, Babak
Abstract: Employing halenium affinity ( HalA ) as a guiding tool, the weak nucleophilic character of alkyl ketones was modulated by the templating effect of a tethered 2‐tetrahydropyranyl(THP)‐protected alcohol towards realizing a bromenium ion initiated spiroketalization cascade. Addition of ethanol aided an early termination of the cascade by scavenging the THP group after the halofunctionalization stage, furnishing monobromospiroketals. Alternatively, exclusion of ethanol from the reaction mixture biased the transient oxocarbenium towards α‐deprotonation that precedes a second bromofunctionalization event thus, furnishing dibrominated spiroketals. The regio‐ and stereoselectivity exploited in the current methodology provides a novel and rapid access to the dibrominated spiroketal motifs exhibited by several natural products. Abstract : Halenium affinity ( HalA ) guided design leads to stereoselective bromospiroketalization of alkyl ketones, templated by a tethered 2‐tetrahydropyranyl(THP)‐protected alcohol. Subtle alteration of the reaction conditions provides either the bromospiroketals or the dibromospiroketals.